CONTROVERSIES ON THE CONSTRUCTION OF FINANCIAL STATEMENTS. - Kemp, Patrick S. (The Accounting Review, 1963)
Abstract This article focuses on controversies regarding the construction of financial statements. One of the primary areas of controversy revolves around a misunderstanding as to who should be expected to use financial statements or, stated differently, to whom the statements should be directed. Many people, both accountants and others, seem to be concerned with the notion that financial statements frequently are not clear and comprehensible to the "man on the street" or the uninformed layman. On the other hand, accountants certainly should strive to improve the usefulness of their statements to informed, qualified users. Such techniques as the use of charts and graphs to supplement conventional statements, the use of comparative statements, and the constant search for more meaningful accounting terminology serve as examples of this type of worthwhile endeavor. Equally clearly, the accounting profession has a concurrent duty to educate the public in the proper use of financial statements.